Geoengineering, Scientific Community, and Policymakers - Joana Castro Pereira (SAGE Open, 2016)
Besides mitigation and adaptation, geoengineering has been emerging as a new approach to deal with the challenges posed by anthropogenic climate change. However, the various definitions and designations for the concept and its clusters, as well as their unclear boundaries with the concepts of mitigation and adaptation, distort and invalidate the existence of a valuable debate in both academic and public contexts. Identifying the current overlaps, and making a comparative analysis with two previous proposals for the categorization of responses to anthropogenic climate change, this article presents a new categorization proposal directed to promote the essential rapprochement between the scientific community and policymakers. This proposal removes the term geoengineering , pointing out the advantages of a debate specifically oriented toward each method in particular. It is also explained how each category should be envisaged, rethinking the importance of international cooperation and stressing the decisive impact that public awareness could play in dealing with this challenge.